OSTEOCHONDROMA OF THE CORONOID PROCESS OF MANDIBLE: Osteochondroma of the Coronoid Process - Ishaque, Maj Muhammad; Ahmed, Waseem; Bukhari, Syed Gulzar Ali (Pakistan Armed Forces Medical Journal, 2010)
Osteochondroma also known as osteocartilagenous exostosis is one of the most common benign tumor of long bones, but rarely found in facial skeleton1. In head and neck region it has been reported in cranial base, posterior surface of maxilla, maxillary sinus, and different areas of mandible including condyle, coronoid process, ramus, body and symphysis2. It is one of the cause of severely limited mouth opening3. Osteochondroma of coronoid process sometimes forms an extraordinary pseudo-arthrosis joint with zygomatic arch, this condition is called Jacob’s disease4